Online used car advertising system / Lim Yeng Chai - Lim , Yeng Chai (2003)
This Online Used Car Advertising System will be developed with the objectives of utilizing the computer and information technology to provide an easy and convenient online car searching or car advertising in Malaysia. This system transcends across time and space, which means time and space will no longer be barriers. Users can search or advertise their cars at a different location and at anytime.This system is a web-based application to provide car advertising and searching services. It consists of two section , namely the user sesction and the administrator section. User section can be divided into two parts, namely the member and the non-member section. Non-member can only view detail of car while members can advertise their cars, search a car and use the 'send email' service that is not provided to non-members. Meanwhile, the administrator section will provide the administrator with facilities to manage record of its members, cars and car category and also to add administrator. The web server for this system is the Internet Information Server(IIS) running under the Microsoft SQL Server while Active Server Pages (ASP) Will be the main programming language technology to develop the system based on the system requirements.